2022
DOI: 10.3389/fgene.2022.928393
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Supplementation Rescues the Social Deficits in Fmr1 Knockout Mice

Abstract: Autism spectrum disorder (ASD) is a heritable neurodevelopmental disorder with the underlying etiology yet incompletely understood and no cure treatment. Patients of fragile X syndrome (FXS) also manifest symptoms, e.g. deficits in social behaviors, that are core traits with ASD. Several studies demonstrated that a mutual defect in retinoic acid (RA) signaling was observed in FXS and ASD. However, it is still unknown whether RA replenishment could pose a positive effect on autistic-like behaviors in FXS. Herei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…Regardless of the treatment, this difference is no longer present in the second test, suggesting that this mild deficit in the sociability index can be restored by repeated exposure to a novel social stimulus. These findings highlight that Fmr1 KO mice do not have a sociability deficiency, consistent with existing literature (Yang et al, 2022). The same is true for Shank3 KO mice, who have been documented to prefer a social target over an inanimate object when subjected to this test (Jaramillo et al, 2017).…”
Section: Male Sociability Is Not Affected In Fmr1 and Shank3 Ko Micesupporting
confidence: 91%
“…Regardless of the treatment, this difference is no longer present in the second test, suggesting that this mild deficit in the sociability index can be restored by repeated exposure to a novel social stimulus. These findings highlight that Fmr1 KO mice do not have a sociability deficiency, consistent with existing literature (Yang et al, 2022). The same is true for Shank3 KO mice, who have been documented to prefer a social target over an inanimate object when subjected to this test (Jaramillo et al, 2017).…”
Section: Male Sociability Is Not Affected In Fmr1 and Shank3 Ko Micesupporting
confidence: 91%
“…We further found identified agents-gene axes using the DSigDB database. The existing studies have shown different types of agents affecting ASD, including those that improve ASD (resveratrol, vitinoin, vitamin E, and retinoic acid) ( 78 82 ) and those that exacerbate ASD (valproic acid, arsenic, benzo[a]pyrene, and acetaminophen) ( 83 86 ). Moreover, there are ASD-related agents with unknown risks, including reagents with neurotoxicity and immunotoxicity (platinum, bortezomib, tert-butyl hydroperoxide, vincristine, atrazine, 7646-79-9, hydrogen peroxide, aflatoxin B1, and copper sulfate) ( 87 95 ) or agents providing neuroprotection and immune regulation (genistein, cyclosporin A, and decitabine) ( 96 98 ) and agents that require exploration in terms of immune and neurological function (hematoxylin and tetradioxin).…”
Section: Discussionmentioning
confidence: 99%
“…In a study published in 2018, vitamin A deficiency was found in 78% of autistic children, and vitamin A supplementation improved autistic symptoms [27]. In a genetic mouse model of autism, retinoic acid treatment rescued social deficits [28]. In a valproateinduced mouse model of autism, prenatal exposure to ascorbate attenuated the effects of valproate on the autistic behaviors of the pups [29].…”
Section: Introductionmentioning
confidence: 99%